(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2020)
The present study was designed to investigate antioxidant, antimicrobial and cytotoxic effects of petroleum ether, chloroform and hydromethanol fraction of methanol extract of Citrus aurantifolia peel. Preliminary phytochemical screening of the fractions was done following the standard procedure. Antioxidant activity was measured using DPPH free radical scavenging assay besides measuring total phenolic and flavonoid content using Folin-Ciocalteu reagent and aluminum trichloride method, respectively. The antimicrobial activity was conducted by disc diffusion method and cytotoxic activity was determined by brine shrimp lethality bioassay. The results of phytochemical screening were indicative of the presence of steroids, alkaloids, saponins, glycosides, flavonoids in the fractions. A dose dependent scavenging activity was observed in DPPH radical scavenging assay where chloroform fraction demonstrated the highest activity with IC50 value of 153.68 ± 3.60 μg/ml. The highest phenolic content was observed in chloroform fraction (308.0 ± 6.55 mg/g gallic acid equivalent) and highest flavonoid content was found in hydromethanol fraction (132.66 ± 2.36 mg/g quercetin equivalent). The chloroform fraction showed excellent antibacterial activity against all the tested bacteria where highest zone of inhibition (19 mm) was produced against Bacillus cereus. In brine shrimp lethality bioassay, LC50 values for petroleum ether, chloroform and hydromethanol fractions were 367.39 μg/ml, 228.14 μg/ml and 296.52 μg/ml, respectively. The present findings suggested that C. aurantifolia peel could be a potent source of medicinally important secondary metabolites and further investigations can be done to identify those active compounds responsible for such bioactivity. Dhaka Univ. J. Pharm. Sci. 19(2): 161-168, 2020 (December)